PERBUATAN MENJANJIKAN PENGHENTIAN PENYIDIKAN OLEH OKNUM POLRI DALAM PENANGANAN SUATU PERKARA DALAM PERPEKTIF UNDANG-UNDANG NO. 20 TAHUN 2001 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI (Studi Putusan Pengadilan Nomor 01/Pid. Sus/2017PN. Mdn) - Hasiholan Simamora; Nelvita Purba; Muhammad Arif Sahlepi (LPPM YPITI, 2021)
The crime of corruption is an extraordinary crime because it is systemic, endemic with a very wide impact which not only harms the state's finances, but also violates the social rights and economic rights of the wider community so that its action needs special efforts. The formulation of the problem in this thesis is how to regulate corruption offenses in Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption, how to qualify offenses and sanctions related to the act of promising to stop case investigations by police officers in the decision Number 01/Pid. Sus/2017/PN. Mdn, what is the basis for the judge's consideration in making a decision against the defendant in the decision Number 01/Pid. Sus/2017/PN. Mdn. The research method used is descriptive analysis that leads to normative juridical legal research, namely research conducted by referring to legal norms, namely researching library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results of the study indicate that the provisions governing the crime of Corruption Crimes in Indonesia are regulated in Law Number 20 of 2001 concerning the Eradication of Corruption Crimes in conjunction with Law Number 31 of 1999 concerning the Eradication of Corruption Crimes. Qualification of offenses and sanctions related to the act of promising to stop the investigation of cases by police officers in decision Number 01/Pid Sus/2017/PN. Mdn is a defendant who has been legally and convincingly proven to have committed a criminal act of corruption. The basis for the judge's consideration in making a decision against the defendant is in the decision Number 01/Pid. Sus/PN. Mdn is based on legal considerations, the element of receiving a gift or promise has been proven and fulfilled convincingly guilty of committing a criminal act of corruption.